Book Review: The Copyright Thing Doesn’t Work Here: Adinkra and Kente Cloth and Intellectual Property in Ghana - Voigts, Matt (Journal of Copyright in Education & Librarianship, 2024)
The Copyright Thing Doesn’t Work Here: Adinkra and Kente Cloth and Intellectual Property in Ghana, by Boatema Boateng, is an excellent case study of the uneasy fit between the global intellectual property (IP) system and postcolonial contexts, as well as a great introduction to challenges in the field for readers seeking more just IP systems. IP makes creative work legible for certain kinds of ownership: it arbitrates who can copy what, and ideally gets somebody paid. But who? The answer, in the case of adinkra and kente cloth, is often not the artisans but the nation-state that claims the work as collectively “Ghanian,” and factories in Asia that scale up production of the designs for their own, cheaper textiles. “IP” overrides the significance of the cloth to its producers and their understandings of copying, appropriate remuneration, and authorship.